Similarities between Arabic kinayah and Malay idioms by the theory of al-Naẓm: a comparison / Abdul Basir Awang, Zulkarnain Mohamed dan Md. Nor Abdullah - Awang, Abdul Basir; Mohamed, Zulkarnain; Abdullah, Md. Nor (Universiti Teknologi MARA, Perlis, 2016)
Similarities of idioms between Arabic (KA) and Malay (KM) can be attributed to external factors and internal language.To explain the elements of true equality, both figurative language will be analyzed with the theory of al-nazm (TN). The main objective of this study was to identify the similarities that exist in KA and KM. Similarities not only facilitate the understanding of Arab kinayah, even make meaning to be conveyed by Allah in the Qur'an in particular can be understood clearly, accurately and comprehensively. KA understanding with relatively KM is a method to keep the main significance and meanings as well as additional structural of idioms. The findings show that there are some similarities between KA and KM in meaning and word structure.